2005
DOI: 10.3168/jds.s0022-0302(05)72990-8
|View full text |Cite
|
Sign up to set email alerts
|

Altering the Fatty Acids in Milk Fat by Including Canola Seed in Dairy Cattle Diets

Abstract: The objective was to evaluate the effects of feeding ground canola seed on the fatty acid profile, yield, and composition of milk from dairy cows. Twenty-four multiparous Holstein cows (548.3 +/- 11.9 kg body weight and 28 +/- 9 d in lactation) were randomly assigned to 1 of 2 treatments: Control (CON) or ground canola seed treatment (GCS) with 14% [of diet dry matter (DM)] of the total ration as ground canola seed containing 34% lipid. Diets contained 20% crude protein, but varied in net energy as a result of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
62
1
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(84 citation statements)
references
References 32 publications
(49 reference statements)
19
62
1
1
Order By: Relevance
“…A lack of change in milk fat trans-11 18:1 content has been reported in cows fed milled rapeseeds even when a similar amount of lipid in the form of rapeseed oil enhanced the concentration of this biohydrogenation intermediate in milk (Givens et al, 2009). Previous studies have also reported that ground rapeseeds have no effect (Collomb et al, 2004) or result in marginal increases in milk fat trans-11 18:1 concentrations (Chichlowski et al, 2005).…”
Section: Kliem Shingfield Humphries and Givensmentioning
confidence: 96%
See 1 more Smart Citation
“…A lack of change in milk fat trans-11 18:1 content has been reported in cows fed milled rapeseeds even when a similar amount of lipid in the form of rapeseed oil enhanced the concentration of this biohydrogenation intermediate in milk (Givens et al, 2009). Previous studies have also reported that ground rapeseeds have no effect (Collomb et al, 2004) or result in marginal increases in milk fat trans-11 18:1 concentrations (Chichlowski et al, 2005).…”
Section: Kliem Shingfield Humphries and Givensmentioning
confidence: 96%
“…Ground rapeseeds have been shown to reduce fat corrected milk yield, milk fat and protein content in the absence of changes in DM intake (Chichlowski et al, 2005). However, supplements of milled rapeseeds and wheat were reported to stimulate higher DM intake compared with the same amount of lipid in the diet as rapeseed oil (Givens et al, 2009).…”
Section: Kliem Shingfield Humphries and Givensmentioning
confidence: 99%
“…This may be due to similar input fiber and energy of the total ration in each of the experiments, as was suggested by Murphy et al (2008). In other study that compared the use of canola seeds treated with alkaline peroxide vs. ground canola grain (2.4 kg d -1 ) in TMR diets, there was no differences on the percentage of milk fat (Aldrich et al, 1997), while the use of ground canola seed compared to canola meal extracted, decreased the percentage of fat (Chichlowski et al, 2005;Neves et al, 2009). Lerch et al (2012a) observed higher milk fat contents in cows receiving cold-pressed fat-rich canola seed meal and whole unprocessed canola seeds compared with other treatments.…”
Section: Milk Yield and Qualitymentioning
confidence: 79%
“…For instance, it has been reported that fresh forage (Khanal et al, 2005;Dewhurst et al, 2006;Butler et al, 2008; Conjugated linoleic acid content in milk of Chilean Black Friesian cows under pasture conditions and supplemented with canola seed (Brassica napus) concentrate Rego et al, 2008) and diets supplemented with plant oils, high in linoleic acid Stanton et al, 2003) increase CLA concentration in milk fat. Within the seeds of oilseeds, rapeseed (Brassica napus) has been used in TMR (total mixed ration) diets in dairy cows (Bayourthe et al, 2000, Chouinard et al, 2001Ward et al, 2002;Chichlowski et al, 2005;Chen et al, 2008;Neves et al, 2009;Lerch et al, 2012b). However, the information about its utilization as a supplement under grazing conditions is limited and contradictory (Stanton et al, 1997;Lawless et al, 1998;Fearon et al, 2004;Lerch et al, 2012b).…”
Section: Introductionmentioning
confidence: 99%
“…The fatty acid composition of canola oil is made up of less than 10% SFA, 8%-10% PUFA in a ratio of linoleic to linolenic acids between 4:1 and 10:1, the remainder being MUFA. Studies have shown that canola has human (Bourre, 2005(Bourre, , 2007Damude & Kinney, 2007;de Lorgeril & Salen, 2004;Flickinger, 2007;Garman, Mulroney, Manigrasso, Flynn, & Maric, 2009;Gebauer, Psota, Harris, & Kris-Etherton, 2006;Ghafoorunissa, 1998;Gillingham, Gustafson, Han, Jassal, & Jones, 2011;Ristić-Medić, Ristić, & Tepsić, 2003) and animal health benefits and have been manipulated in animal diets to produce fat healthy animal products for human consumption (Bourre, 2005;Chichlowski, Schroeder, Park, Keller, & Schimek, 2005;Meadus et al, 2010). As with flaxseed,…”
mentioning
confidence: 99%